2003
DOI: 10.1520/jfs2001400
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Age in Adolescents—The Basilar Synchondrosis

Abstract: The state of fusion of the basilar synchondrosis as a biological age indicator was assessed in a sample of 91 cadavers of both sexes whose ages ranged between 8 and 26 years. The correlation between the degree of closure and chronological age was investigated. Although the female population sample was very small (n = 21), the data indicate a tendency of differences in age between the "open" and "closed" groups. In the male population (n = 70), no significant differences were detected between the “open” and “cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 13 publications
2
31
0
1
Order By: Relevance
“…30 But Kahana et al found no correlation between chronological age and the closure degree of the synchondrosis in males, although in females they found it a possible reliable indicator of age but they had a small sample comprising of 21 females. 2 We tried to examine a large sample of both sexes in this study. Our results showed that the closure degree of Spheno-occipital suture has a linear correlation with age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30 But Kahana et al found no correlation between chronological age and the closure degree of the synchondrosis in males, although in females they found it a possible reliable indicator of age but they had a small sample comprising of 21 females. 2 We tried to examine a large sample of both sexes in this study. Our results showed that the closure degree of Spheno-occipital suture has a linear correlation with age.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Ethnical differences that have been among Kahana et al materials may be responsible to their wide discrepancy of synchondrosis fusion time. 2 We examined the state of fusion of the basilar synchondrosis as a biological age indicator in a sample of 376 cadavers of both sexes whose ages ranged between 8 and 26 years. Our findings indicated that the stage of fusion of the basilar synchondrosis can be a useful indicator of age in male and female cadavers, when estimating age of unknown human remains, although further investigation on different ethnic population is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the degree of accuracy of the age estimate is inversely proportional to the length of time lived (11) and hence, biologic estimations of age are the most accurate in the early phases of development. Secondly, there are only two types of macroscopic parameters that are useful indicators of biological age: firstly, epiphyseal closure throughout the skeleton and secondly, dental age (12). Unfortunately, skeletal maturation is not well correlated with chronological age, nor are its underlying genetic processes well buffered, as they are known to be influenced by environment, lifestyle, and activity (e.g.…”
Section: Discussionmentioning
confidence: 99%